FRI0417 Cd86 expression on cultured skin fibroblasts from systemic sclerosis patients: in vitro effects of ctla4-ig. (12th June 2018) - Cutolo, M.; Montagna, P.; Soldano, S.; Trombetta, A.C.; Contini, P.; Ruaro, B.; Sulli, A.; Scabini, S.; Stratta, E.; Brizzolara, R.
Abstract : Background: Skin fibroblasts (SFs) are involved in the excessive production of extracellular matrix (ECM) proteins which characterises fibrosis in systemic sclerosis (SSc). 1 Myofibroblasts which are characterised by a higher expression of pro-fibrotic molecules (a-SMA: alpha-smooth muscle actin; S100A4: fibroblast-specific protein-1) as well as by the over-production of ECM proteins (FN: fibronectin; collagens type I and III), may originate from the activation and differentiation of resident fibroblasts after multiple profibrotic stimuli. 2 CTLA4-Ig interacts with the cell surface costimulatory molecule CD86 and can downregulate the target cell activation. 3 Objectives: To evaluate CD86 expression and the in vitro effects of CTLA4-Ig on skin fibroblasts (SFs). Methods: Skin biopsies were obtained from 8 "limited" cutaneous SSc patients (treated only with vasodilators, mainly cyclic prostanoids) and 4 healthy subjects (HSs), after EC and patient informed consent. After 8 days (T8) of culture, SFs obtained from biopsies were treated for 24 and 48 hours, in the absence or in the presence of CTLA4-Ig (10, 50, 100 and 500 micrograms/ml). Evaluation of CD86 expression was performed by quantitative real-time polymerase chain reaction (qRT-PCR). In addition, also human macrophages obtained from PBMCs of SSc patients, were cultured. The statistical analysis was carried out by the non-parametric Mann-Whitney U test. Results: Cultured SSc fibroblasts showed a very low gene expression level of CD86, compared to cultured macrophages of SSc patients, taken as positive control for CD86 expression (99% less). Therefore, cultured SSc fibroblasts treated for 24 hours and for 48 hours with CTLA4-Ig (10, 50, 100 and 500 micrograms/ml) did not show any significant modulation in the gene expression levels of CD86, compared to untreated fibroblasts (CNT). Interestingly, cultured HSs fibroblasts treated with CTLA4-Ig for 24 hours and for 48 hours showed a significant decrease in the gene expression of CD86, limited to the highest dose (500 micrograms/ml), compared to CNT (0.16% and 0.64% less, respectively) (p<0.05). Conclusions: In the present short-term study (24 and 48 hours), no significant effects at qRT-PCR resulted after CTLA4-Ig treatment of cultured SSc SFs. The result might arise from a limited expression of CD86, as consequence of a retained advanced differentiation of the the SSc fibroblasts. On the contrary, a significant reduction of CD86 expression on HSs fibroblasts treated with CTLA-4Ig was observed. References: [1] Asano Y. J Dermatol2017. Epub ahead of print. [Review]. [2] Hin ZB, Phan SH, et al. Am J Pathol2007;170:1807–16. [3] Cutolo M, et al. Arthritis Res Ther2009;11:176–85. Acknowledgements: Disclosure of Interest: M. Cutolo Grant/research support from: BMS, Actelion, Celgene, Boehringer, P. Montagna: None declared, S. Soldano: None declared, A. C. Trombetta: None declared, P. Contini: None declared, B. Ruaro: None declared, A. Sulli: None declared, S. Scabini: None declared, E. Stratta: None declared, R. Brizzolara: None declared